Changes in Post-migration Living Difficulties Predict Treatment Outcome in Traumatized Refugees - Schick, Matthis; Morina, Naser; Mistridis, Panagiota; Schnyder, Ulrich; Bryant, Richard A.; Nickerson, Angela (Frontiers in Psychiatry, 2018)
Background: Refugee mental health is affected by traumatic stressors as well as post-migration living difficulties (PMLD). However, their interaction and causal pathways are unclear, and so far, no distinct treatment recommendations regarding exile-related stressors exist. Methods: In a 3-year follow-up study, PMLD and symptoms of post-traumatic stress (PTS), depression and anxiety were examined in a clinical sample of severely traumatized refugees and asylum seekers (N=71). Results: In regression analysis, reduction in PMLD predicted changes over time in depression/anxiety. The opposite models with PMLD changes as outcome variable, and change in PTS and depression/anxiety as the predictor variables, proved not to be significant. Conclusions: In addition to well-established trauma-focused interventions for the treatment of PTS, psychosocial interventions focusing on PMLD might contribute to a favorable treatment response in traumatized refugees, particularly with regard to depression and anxiety.